PERKEMBANGAN SOSIAL EMOSIONAL DAN PERKEMBANGAN BAHASA AUD PASCA MASA PANDEMI - syisva nurwita; Ranny Fitria Imran (Jurnal PG-PAUD, 2021)
The pandemic period is a period that can affect the development of early childhood experiencing limitations in various activities, including playing while learning in Early Childhood Education hich results in a decline in children's social-emotional development and language development. The ability to speak is an ability that is acquired naturally, speaking formally requires an incentive process of training and direction and can be done through playing activities in PAUD AIZA. Problems in children's language development affect children's social emotional development. Social emotional development of children is one aspect of development that must be achieved by early childhood. Children's emotional social maturity can be seen the extent to which children can be well received in their social environment. The purpose of this study was to determine the social, emotional and language development of early childhoot after the pandemic. Through classroom action research methods can improve the social emotional development and language development of children. After the social-emotional and language development of early childhood during the pandemic, this is very low, this is due to several factors, including children who have not seen friends for too long, so activities that can help children's social-emotional and language development do not work as they should. Researchers took steps to conduct research using the classroom action method, while the results obtained were 80.89% with very well developed criteria.Masa pandemic merupakan masa yang dapat mempengeruhi perkembangan anak usia dini, selama pandemic anak mengalami keterbatasan dalam berbagai kegiatan, diantaranya bermain sambil belajar di PAUD yang mengakibatkan perkembangan social emosional dan perkembangan bahasa anak menurun. Kemampuan berbicara merupakan kemampuan yang didapat secara alamiah, tetapi berbicara secara formal memerlukan proses latihan dan pengarahan yang insentif dan dapat dilatih melalui kegiatan selama kegiatan bermain di PAUD AIZA. Permasalahan dalam perkembangan bahasa anak mempengaruhi perkembangan social emosial anak. Perkembangan sosial emosional anak merupakan salah satu aspek perkembangan yang harus dicapai anak usia dini. Kematangan sosial emosi anak dapat terlihat sejauh mana  anak dapat diterima secara baik dilingkungan sosialnya. Tujuan penelitian ini adalah untuk mengetahui perkembangan social emosional dan bahasa anak usia dini pasca masa pandemic. Melalui metode penelitian tindakan kelas dapat meningkatkan perkembangan social emosional dan perkembangan bahasa anak. Perkembangan sosial emosional dan bahasa anak usia dini pasca masa pandemic sangat rendah, hal ini disebabkan beberapa faktor diantaranya anak sudah terlalu lama tidak bertemu dengan teman-teman sehingga kegiatan yang dapat membantu perkembangan social emosional dan bahasa anak tidak berjalan sebagaimana mestinya. Peneliti mengambil langkah melakukan penelitian dengan metode tindakan kelas, adapun hasil yang didapat  sebesar 80,89% dengan kriteria berkembang sangat baik.Kata Kunci: Perkembangan, Sosial Emosional, Bahasa DOI: http://dx.doi.org/10.23960/jpa.v7n2.23071